Woman and political work in the Islamic contemporary thought - Al-Shoobake, AbedAlraheem (Journal of Humanities & Social Sciences, 2020)
This study analyst woman subject and political work in the Islamic contemporary thought; so the study aims at exploring the participation of the Islamic contemporary political thought in renewing its thesis about woman subject and political work ; moreover; the study embrace context analysis method ;so it represents the Islamic contemporary contexts and thought. It is based on the Islamic intellectual positions, that in some cases recognizes the involvement of women in politics, and some other deny it.Therefore; this study reached the conclusion that there is no religious prohibition which prohibit woman to take part in any position in society or state. And so she has the right or the big must and duty to take part in the political life as well as in the parliamentary councils and presidency of the state.
Keywords: women and political work; contemporary Islamic thought; women and political participation; women and parliament; women and the presidency of the state